Bioconvection and melting behavior of nano-enhanced phase change materials water nanofluid in a sinusoidally heated porous chamber with oxytactic microorganisms - Rajesh, Vemula; Öztop, Hakan Fehmi (Springer, 2025)
This study investigates the coupled mechanisms of bioconvection and phase-change heat transfer in a porous chamber saturated with Nano-Encapsulated Phase-Change Material (NEPCM)-water nanofluid containing oxytactic microorganisms. The chamber is bounded by a sinusoidally heated, oxygen-permeable bio-coated left wall and a cooled, oxygen-permeable bio-coated right wall, while the horizontal walls are adiabatic and impermeable. This configuration enables simultaneous analysis of latent-heat exchange by NEPCM capsules, microorganism-induced buoyancy, and momentum resistance within the porous matrix. A Galerkin finite-element formulation is employed to solve the coupled nonlinear equations derived from the Darcy-Brinkman-Forchheimer model and bio-convective transport theory. The effects of the Rayleigh number (Ra), bioconvection Rayleigh number (Rb), Darcy number (Da), Lewis number (Le), Peclet number (Pe), Stefan number (Ste), and fusion temperature (theta f) are examined to characterize flow, heat, and mass-transfer behavior. The results indicate that heat and mass transfer intensify significantly with increasing Ra, Rb, and Da, with Da exerting the dominant influence, enhancing the average Nusselt number by over 380%. Optimal ranges of Le and Pe are identified for maximizing oxygen diffusion and microorganism transport. The findings provide new physical insight into biothermally active porous systems and offer design guidance for hybrid bio-nanofluidic and thermal-energy-storage devices employing NEPCM-based suspensions.
Keywords: Nano-encapsulated phase change materials (NEPCMs)-water nanofluid; Bioconvection; Oxytactic microorganisms; Porous medium; Darcy-Brinkman-Forchheimer model; Finite element method